Rancang Bangun Media Sestea (System E-Learning Smart Teaching) Berbasis Website Dengan Model Pembelajaran Pjbl Untuk Meningkatkan Kompetensi Administrasi Infrastruktur Jaringan Pada Siswa Kelas Xi Tkj Di Smkn 1 Sidayu Gresik - Muhammad Iqbal Haqiqi; Susanti, Martini Dwi Endah (IT-Edu : Jurnal Information Technology and Education, 2025)
The learning media developed by the researcher, named SESTEA, aims to examine the differences in cognitive and psychomotor competencies of students in the subject of Network Administration between website-based learning with the PJBL model and conventional learning. This study employs a Research and Development approach by adapting the ADDIE model. The experimental design used in this study is a Quasi-Experimental model with a Pretest-Posttest Control Group Design. The learning media is developed using PHP 8.3 for the back-end, React JS for the front-end, the Laravel framework, and MySQL database. Validation of the lesson plans, media, questions, and materials showed validity levels of 87%, 91%, 91%, and 96%, respectively. The average posttest score for cognitive skills is higher than the pretest score, with 78.7 > 48.4. Similarly, the average posttest score for psychomotor skills is higher than the pretest score, with 78.9 > 38.6. The hypothesis test results using the paired sample t-test show a Sig. (2-tailed) There is a significant difference in the learning results of students who used the website-based SESTEA learning medium compared to those who did not, in the topic of Network Administration, with a value of 0.000 < 0.05, indicating that is rejected and is approved.